High-precision clock synchronization based on PSO algorithm under the small sample condition - Yilin Jiang; Fangyuan Zhang; Muran Guo (2016 IEEE Advanced Information Management, Communicates, Electronic and Automation Control Conference (IMCEC), 2016)
In order to solve the problem of clock synchronization under the condition of small sample set, a state optimal estimation method of data fusion bases on natural selection PSO algorithm is proposed. First, use Kalman filtering algorithm and Bootstrap method to local filtering process the measurement data under the condition of Monte Carlo simulation experiment, and the reliability of the data is improved. Then, use natural selection PSO algorithm to fuse the data, the optimal fused estimation is achieved and the fusion accuracy is improved. Finally, the fusion result is considered as the new information of virtual master clock, which could exchange time messages with node clock of network from the algorithm. Thus, clock synchronization in the network is realized. The simulated results show that the accuracy is improved. High precision clock synchronization is realized and the stability time is decreased.